Are There Types of Academically Entitled Students? A Cluster Analysis - Jackson, Dennis L.; McLellan, Chelsea; Frey, Marc P.; Rauti, Carolyn M. (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Academic entitlement (AE), which includes some students’ tendencies to express deservingness of academic outcomes, not based on achievement, may have serious implications, such as academic dishonesty and classroom incivility. Some researchers have suggested that there may be different types of students with regard to AE, implying that motives for entitled behaviour may not be uniform. The current study extends previous work in identifying subtypes of AE. A sample of 751 undergraduate students responded to measures of AE, narcissism, and performance avoidance learning orientation. Cluster analysis revealed five distinct clusters: Entitled Narcissist, Entitled Non-Narcissist, Unobtrusive Entitlement, Not Entitled, and Performance Avoidant. The Entitled Narcissist cluster is small in size and members generally have a higher sense of entitlement. The Entitled Non-Narcissist cluster is larger in size and members tend to have high performance avoidance scores. Understanding typologies of AE could lead to different strategies for addressing highly entitled students. Keywords: academic entitlement, student entitlement, cluster analysis, typologies